2017
DOI: 10.3390/machines5010004
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Embedded Machine Learning: Case Study with Electrochemical Micro-Machining

Abstract: Abstract:Although intelligent machine learning techniques have been used for input-output modeling of many different manufacturing processes, these techniques map directly from the input process parameters to the outputs and do not take into consideration any partial knowledge available about the mechanisms and physics of the process. In this paper, a new approach is presented for taking advantage of the partial knowledge available about the mechanisms of the process and embedding it into the neural network st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…To initialize the tuning parameter boundary, a trial-and-error based approach was implemented to determine the basic structure of the deep convolution network. The structure of the network refers to the previous work in [11,27,28] with an added convolutional layer and dropout layer to add nonlinearity and prevent overfitting. The network was initialized with a convolutional layer and one dense layer with 20 neurons.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To initialize the tuning parameter boundary, a trial-and-error based approach was implemented to determine the basic structure of the deep convolution network. The structure of the network refers to the previous work in [11,27,28] with an added convolutional layer and dropout layer to add nonlinearity and prevent overfitting. The network was initialized with a convolutional layer and one dense layer with 20 neurons.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the deep CNN yields the minimum error among all four models. In addition, by comparing Figures 4 and 6, it can be observed To validate our proposed model, the networks developed in [11,27,28] were compared with the proposed CNN. The mean least square support vector regression machines in [31] were also added for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations